2020
DOI: 10.23736/s0021-9509.19.11199-8
|View full text |Cite
|
Sign up to set email alerts
|

Current results of balloon expandable visceral stent-grafts in fenestrated endografting

Abstract: INTRODUCTION: endovascular repair of thoracoabdominal and juxtarenal aortic aneurysm has recently become a valuable alternative to open surgery especially in high-risk patients.Progressive improvements in graft materials and low-profile devices allow treatment of complex aneurysms even in adverse anatomical settings. However, all published experiences report risks of occlusion and reinterventions due to visceral stent-graft failures in the long term. The purpose of this systematic review is to analyze the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…12 BeGrafts have been chosen as bridging stent grafts for their low profile and the wide range of available lengths. 13 Residual type IIIc endoleak, decreased after first relining and then left untreated, may have occurred because fenestrations had been designed too large to decrease the risk of misalignment and failure to cannulate, but insufficient flaring of the mating stent graft was then not able to cope with the gap between the aortic and the visceral components. The procedure was, however, successful in promoting a false lumen thrombosis in the thoracic portion of the fissured TAAA, with a successful clinical result.…”
Section: Discussionmentioning
confidence: 99%
“…12 BeGrafts have been chosen as bridging stent grafts for their low profile and the wide range of available lengths. 13 Residual type IIIc endoleak, decreased after first relining and then left untreated, may have occurred because fenestrations had been designed too large to decrease the risk of misalignment and failure to cannulate, but insufficient flaring of the mating stent graft was then not able to cope with the gap between the aortic and the visceral components. The procedure was, however, successful in promoting a false lumen thrombosis in the thoracic portion of the fissured TAAA, with a successful clinical result.…”
Section: Discussionmentioning
confidence: 99%
“…The stent is fully encapsulated in the fluoropolymer and the inner surface is covered with a stable, covalently bound bioactive heparin of porcine origin. 2,11,15 The Advanta V12 (Getinge) endoprosthesis is a balloon-expandable stent-graft. It is characterized by a stainless-steel stent encapsulated in an ultrathin PTFE fabric.…”
Section: Description Of the Stent-graftsmentioning
confidence: 99%
“…Gore Inc, Flagstaff, AZ, USA) stent-graft has been introduced, with the potential to be used as bridging stent for fenestrated endografting. 1013 In vitro studies have demonstrated an excellent impermeability and resistance to pull-out and shear forces in a fenestrated graft model. 9,14 However, fracture resistance to cyclic movement/loading over the time has not been evaluated so far.…”
Section: Introductionmentioning
confidence: 99%
“…Visceral stent-grafts in different configurations (balloon expandable or self-expanding stent-grafts, eventually re-enforced by bare metal stents) were chosen in each dingle case depending on the vessel anatomy. Usually balloon expandable stent-graft was used for fenestrations (Advanta V12, Getinge; BeGraft, Bentley InnoMed) and self-expanding stent was used for branches (Fluency, Bard) [19]. Target vessels were engaged from a femoral access in case of fenestrations, while a brachial approach was used for branches.…”
Section: Endovascular Proceduresmentioning
confidence: 99%